Visuoconstructional Impairment in Dementia Syndromes - William E. Reichman; Jeffrey L. Cummings; Keith D. McDaniel; Frederick Flynn; Jeffrey Gornbein (Behavioural Neurology)
Dementia of the Alzheimer type (DAT) affects most neuropsychological domains including language, memory, and visuo-spatial skills. The latter are usually assessed by poorly quantifiable copying tasks. We assessed constructional abilities using the Developmental Test of Visuomotor Integration (VMI) comprised of a series of model drawings of increasing complexity. Twenty-six patients meeting NINCDS-ADRDA criteria for DAT, 21 normal aged subjects with normal mental status examinations, and 14 patients with vascular dementia were tested. In DAT, we found significant correlations between visuoconstructive ability and memory registration, delayed recall, and language functions such as confrontation naming and word-list generation. Less marked, but significant correlations were found in the vascular dementia group between visuoconstructive ability and memory registration and word-list generation. A few normal elderly subjects were unable to copy the most challenging figures. The study demonstrates that: (1) VMI is a convenient method for quantifying constructional deficits in DAT and other dementing illnesses; (2) constructional deficits are highly correlated with dementia severity and memory and language deficits in DAT; (3) neuropsychological deficits are less highly inter-correlated in vascular dementia than in DAT; and (4) abnormal constructional skills are present in some normal elderly.